The Implementation of Planning and Budgeting System Redesign in Efforts to Reform Planning and Budgeting - Kartika Sukma Oktanidya (Jurnal Indonesia Sosial Teknologi, 2024)
The Redesign of the Planning and Budgeting System (RSPP) is one of the government's efforts to realise effective and efficient planning and budgeting at the central and regional levels. The implementation of RSPP is expected to be able to answer problems in the planning and budgeting system, including the inconsistency of central and regional expenditure programs, differences in programs used in planning and budgeting documents, the formulation of program nomenclature and normative outcomes, and development performance information in planning and budgeting documents that are difficult for the public to understand. However, in its implementation, there are still problems faced by Ministries/Institutions so the Ministry of Finance together with the Ministry of National Development Planning/Bappenas need to periodically eval_uate the formulation of RSPP in Ministries/Institutions through the Work Plan and Budget documents that have been issued. The process of improving the implementation of RSPP in Ministries/Institutions is followed by improving the guidelines and rules that oversee the implementation of RSPP in Indonesia. Several policies need to be taken to support the implementation of RSPP, namely the Logical Framework policy in the Formulation of Performance and Performance Indicators as well as the Synchronization of Planning and Budgeting Documents through the Integration of Planning and Budgeting Applications so that planning and budgeting documents become harmonious and easy to understand. For the implementation of RSPP to be effective and efficient, the Ministry of Finance together with the Ministry of National Development Planning/Bappenas need to periodically eval_uate the performance information that has been prepared by the Ministries/Institutions by the Regulation on the Implementation of Planning and Budgeting System Redesign.